Mark Fellowes: "We must learn to reduce our demands on the ecosphere, but I'm not sure that we're smart enough to do that" (Terr@ Plural, 2019)
Entrevista com Dr. Mark Fellowes, da Universidade de Reading, realizada por Dr. Fabio Angeoletto (UFMT).